Cu and Cd concentration in the water, sediment, and Tubifex sp. living in the Sail River, Pekanbaru - Daghista Putri Pawestri; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract             Sail River is one of the polluted rivers by heavy metalsin Riau. High Cu and Cd concentration in the water and sediment may affects the living of organisms in the rivers, including silk worm. A research aims to understand Cu and Cd concent in the water, sediment and silk worm (Tubifex sp.) in that river was conducted in December 2017 – January 2018. Samples of water, sediment and silk worm were taken from three stations; in the upstream (Station 1), in the residential area (Station 2) and in the downstream (Station 3). Samplings were conducted 3 times, once/ 2 weeks. Results shown that the concentration of Cu in the water, sediment and silk worm were 0.004 to 0.092 mg/L, 7.210 to 12.103 mg/kg and 6.702 to 15.228 mg/kg respectively. While the Cd concentration in the water, sediment and silk worm were 0.005 to 0.014 mg/L, 0.417 to 0.917 mg/kg and 0.350 to 2.550 mg/kg respectively. It was concluded that the water, sediment and silk worms from the Sail River were already contaminated with Cu and Cd. Keyword : heavy metals, polluted river, silk worm, Copper, Cadmium